Cross-national patterns in individual and household employment and work hours by gender and parenthood - Joya Misra; Michelle Budig; Irene Böckmann (Luxembourg Income Study (LIS), 2010)
We distinguish between overall employment rates and full-time employment rates among men and women, and examine total household employment hours for heterosexually partnered men and women, as well as women's share in total household employment hours, to investigate how gender, parenthood, and partner's employment are related to individual's employment patterns. We use data from LIS from around 2000 for 19 countries, examining former East and West Germany separately. With a sample restricted to adults aged 25 to 45 (prime years for childrearing), who are not in the military, we analyze employment patterns for individuals and patterns for households, to consider how gendered negotiations around employment hours plays out within households. We make three main arguments. First, gender is less salient than gendered parenthood in explaining differences in men's and women's employment rates. Secondly, it is important to consider both mothers' employment rates and average weekly hours of employment, in order to take into account how mothers' experiences vary cross-nationally both in terms of whether they are able to remain in the labor market, and, for those who remain, how many hours they work. Thirdly, we show that childless couples employment hours are relatively similar across countries, while coupled mothers' and fathers' employment hours vary more cross-nationally - suggesting that different policy contexts are particularly important for explaining cross-nationally variations in parents' employment patterns. We use these three arguments to develop our own models of work-time regimes for heterosexually partnered households that balance gender equity in the division of employment hours against total household hours, and illustrate the major cross-national differences in how men's and women's employment patterns are related.
Keywords: 330; Eltern; Gleichberechtigung; Erwerbstätigkeit; Beschäftigungssystem; Haushaltsproduktion; OECD-Staaten